Solid‐State Far‐Ultraviolet C Light Sources for the Disinfection of Pathogenic Microorganisms Using Graphene Nanostructure Field Emitters - Yoichiro Neo; Gai Hashimoto; Rei Koike; Takashi Ohhara; Takahiro Matsumoto (Global Challenges, 2023)
Abstract The ongoing global outbreak of coronavirus disease has necessitated the use of ultraviolet (UV) disinfection techniques to reduce viral transmission in public places. The previously used UV wavelength is harmful to the human body, the wavelength range from 200 to 235 nm, often referred to as far‐UVC light, has attracted attention as a novel disinfection wavelength range that can be used in a safe manner. However, the currently used light sources have practical problems, such as an expensive cost, a low efficiency, and short lifetimes. Therefore, environmentally friendly solid‐state light sources with a lower cost, higher efficiency, and longer lifetimes are demanded. Here, an efficient mercury‐free far‐UVC solid‐state light source is presented. This light source demonstrates intense 230 nm emission with a narrow spectral width of 30 nm and a long lifetime of more than 1000 h. These characteristics can be achieved by graphene nanostructure field emitters and wide‐bandgap magnesium aluminate phosphors. By using this light source, the efficient disinfection of Escherichia coli is demonstrated. The light sources presented here facilitate future technologies for preventing the spread of infectious diseases in a safe and convenient manner.